Eficiencia y precision del diseno en latices bajo distinto numero de repeticiones y tamano de parcela en ensayos de rendimiento de frijol (Phaseolus vulgaris L.) - Amézquita, María Cristina; Muñoz, J.E.; Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1977)
A yield trial with 25 black bean varieties was carried out on the CIAT experimental farm (Palmira, Colombia) to ascertain the efficiency and accuracy of a 5 x 5 lattice design with different no. of replications (2-6) and plot sizes (1, 2, 4 and 6 rows/plot with 1.5, 3.0, 6.0 and 9.0 m(2) areas, respectively). Coefficient of variance (CV), least significant difference (LSD) and relative efficiency (RE) of the lattice design were compared to a randomized complete block design (RCB), CV decreased with increasing plot size for any no. of replications; it ranged from 21-39 percent in one- row plots but was 12 percent in all others. LSD for yield was influenced by the no. of replications: with 2 replications there was an av difference in yield of 604.7 kg/ha; with 6 replications, it was 343,8 kg. LSD was also highly sensitive to changes in plot size: differences decreased with increasing no. of rows/plot. No clearly defined RE tendency was observed in the lattice design as compared to the RCB. The lattice design was as effective as the RCB or more so. (CIAT)